Effects of feeder design, wet-dry feeder adjustment strategy, and diet type on the growth performance and carcass characteristics of growing-finishing pigs - Bergstrom, J.R.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 1,287 pigs (PIC 337 × 1050, initially 82.7 lb) were used to compare the effects of a conventional dry feeder, 3 wet-dry feeder adjustment strategies, and 2 diet types on growing-finishing pig performance. There were 27 pigs per pen and 6 pens per treatment. The first wet-dry strategy consisted of maintaining a setting of 18 throughout the study (WD18). The second wet-dry strategy consisted of an initial setting of 18 until d 56 followed by a reduced setting of 14 for the remainder of the experiment (WD14). The third wet-dry strategy consisted of an initial setting of 18 until d 28, a setting of 14 until d 56, and a setting of 10 for the remainder of the experiment (WD10). The conventional dry feeder remained at a setting of 8 throughout the study. The 2 diet types evaluated in this study were a corn-soybean meal-15% DDGS diet and a corn-25% DDGS-20% bakery by-product-soybean meal diet; both diets were fed over 4 dietary phases. Overall (d 0 to 92), all pigs fed using the wet-dry feeder had greater (P < 0.001) ADG, ADFI, and final BW than pigs fed with the conventional dry feeder. However, within the wet-dry treatments, pigs fed with WD14 and WD10 had a reduced (P < 0.05) ADG compared with pigs fed with WD18. Additionally, ADFI of pigs fed using WD10 was lower (P < 0.05) than that of pigs fed with WD18, and ADFI of pigs fed with WD14 was intermediate. There were no differences in F/G among feeder treatments, and growth performance was similar between the 2 diet types. Pigs fed using the wet-dry feeder had greater (P < 0.02) HCW, yield, backfat depth, revenue per pig, and feed cost per pig than pigs fed with the conventional dry feeder. The loin depth of pigs fed using the wet-dry feeder was less (P < 0.04) than that of pigs fed with the conventional dry feeder. Differences in backfat and loin depth resulted in pigs using the wet-dry feeder having a lower (P < 0.001) fat-free lean index (FFLI) than pigs fed with the conventional dry feeder. However, within the wet-dry feeder treatments, pigs fed with WD10 had a reduced (P < 0.05) backfat depth and increased (P < 0.05) FFLI compared with pigs fed with WD18. The backfat depth and FFLI of pigs fed with WD14 were intermediate. Although not significantly different, income over feed cost was numerically greatest for pigs fed using WD10, followed by conventional dry, WD18, and WD14. In conclusion, reducing the wet-dry feeder setting in later growth periods may improve carcass leanness while maintaining the advantages in growth rate.
Keywords: Swine; Conventional feeder; Feeder adjustment; Wet-dry feeder